ASSOCIATION OF EXERCISE ADDICTION WITH EMOTIONAL DISTRESS AMONG INJURED OR NON-INJURED REGULAR EXERCISORS (The Research of Medical Science Review, 2025)
BackgroundExercise addiction is an undesirable fixation on physical wellness and exercise. It's frequently an aftereffect of self-perception issues and dietary problems. In exercise addiction we cope mood disorder with physical activity. Many sports man was suffering in depression and anxiety due to injury. So, this study was conducted to see the relation between depression and exercise addiction among injured and non-injured exercisers. ObjectiveTo find out the association of exercise addiction with emotional distress among injured or non-injured regular exercisers.MethodologyThis was the cross-sectional study in which continent sampling technique was used to To find out the association of exercise addiction with emotional distress among injured or non-injured regular exercisers. Sample Participants selected in this study on basis of inclusion and exclusion criteria. Analysis of data was conducted by SPSS version 21.ResultsIn this study we find out that the minimum age is 18(0.6%) and maximum is 64(0.6%) respectively. Compared with LREA-exercisers, more HREA exercisers were depressed In current study we also see that 33(20.25%) are at low risk and 7(4.29%) are at high risk of exercise addiction with no symptoms of emotional stress. 79(48.47%) are at low risk and 44(26.99%) are at high risk of exercise addiction with symptoms of emotional stress. There is significant association between PSS and EAI category (p-value = 0.032).ConclusionIn end it was concluded that that the depression and emotional stress is more common among high-risk exercise addition individuals. And the risk of depression and mental illness is increased with musculoskeletal injury. Mental appraisal and advising might be helpful enhancements to substantial injury intercessions for tending to enthusiastic trouble